A coordinate‐based meta‐analytic model of trauma processing in posttraumatic stress disorder. Issue 12 (30th August 2012) - Ramage, Amy E.; Laird, Angela R.; Eickhoff, Simon B.; Acheson, Ashley; Peterson, Alan L.; Williamson, Douglas E.; Telch, Michael J.; Fox, Peter T.
<x xml:space="preserve">Abstract</x> Posttraumatic stress disorder (PTSD) has a well‐defined set of symptoms that can be elicited during traumatic imagery tasks. For this reason, trauma imagery tasks are often employed in functional neuroimaging studies. Here, coordinate‐based meta‐analysis (CBM) was used to pool eight studies applying traumatic imagery tasks to identify sites of task‐induced activation in 170 PTSD patients and 104 healthy controls. In this way, right anterior cingulate (ACC), right posterior cingulate (PCC), and left precuneus (Pcun) were identified as regions uniquely active in PTSD patients relative to healthy controls. To further characterize these regions, their normal interactions, and their typical functional roles, meta‐analytic connectivity modeling (MACM) with behavioral filtering was applied. MACM indicated that the PCC and Pcun regions were frequently co‐active and associated with processing of cognitive information, particularly in explicit memory tasks. Emotional processing was particularly associated with co‐activity of the ACC and PCC, as mediated by the thalamus. By narrowing the regions of interest to those commonly active across multiple studies (using CBM) and developing a priori hypotheses about directed probabilistic dependencies amongst these regions, this proposed model—when applied in the context of graphical and causal modeling—should improve model fit and thereby increase statistical power for detecting differences between subject groups and between treatments in neuroimaging studies of PTSD. Hum Brain Mapp 34:3392–3399, 2013. © 2012 Wiley Periodicals, Inc.